2017
DOI: 10.1111/mec.14133
|View full text |Cite
|
Sign up to set email alerts
|

Using relatedness networks to infer contemporary dispersal: Application to the endangered mammal Galemys pyrenaicus

Abstract: Information about the degree of contemporary dispersal is important when trying to understand how populations interchange individuals and identify the specific barriers that prevent these movements. In the case of endangered species, this can represent crucial information when designing appropriate conservation strategies. Here we analyse relatedness between individuals from different localities and use these data to infer whether dispersal occurred in recent generations. We applied this approach to the Pyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 82 publications
10
61
0
Order By: Relevance
“…Additionally, mean relatedness for female dyads from the same locality was significantly higher than for males, pointing to a higher degree of female philopatry. In a previous study of the Pyrenean desman in the Iberian Range (see Figure a for the location of this population), similar relatedness values were found for female and male dyads (Escoda et al, ); these different results may be explained because overall relatedness within the same locality and inbreeding were much higher in the Iberian Range, probably due to more serious dispersal problems than in the area studied here.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, mean relatedness for female dyads from the same locality was significantly higher than for males, pointing to a higher degree of female philopatry. In a previous study of the Pyrenean desman in the Iberian Range (see Figure a for the location of this population), similar relatedness values were found for female and male dyads (Escoda et al, ); these different results may be explained because overall relatedness within the same locality and inbreeding were much higher in the Iberian Range, probably due to more serious dispersal problems than in the area studied here.…”
Section: Discussionsupporting
confidence: 84%
“…However, these approaches, based on the monitoring of individuals during usually brief time periods, allow small movements to be easily recorded while large‐distance movements, if present, are more difficult to detect, so a complete overview of the dispersal patterns of this species is still lacking. The strategy introduced by Escoda, González‐Esteban, Gómez, and Castresana (), based on the analysis of the relatedness networks of individuals, allowed the study of effective contemporary dispersal over a larger area and through several generations. These authors found low levels of inter‐river dispersal compared to intra‐river dispersal, demonstrating that desmans do not frequently move between different river basins.…”
Section: Introductionmentioning
confidence: 99%
“…The closest study found to ours was by Escoda et al. (), who assessed a genotyping‐by‐sequencing data set for estimating relatedness based on perfectly genotyped simulations. Similar to our study, they found all estimators had >0.97 correlation to true relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…The alarming decline of G. pyrenaicus populations over the recent decades across its whole range Gisbert and García-Perea, 2014) has encouraged local, national and European conservation initiatives (e.g., in France: Life+ Desman, 2013;Némoz et al, 2011). Yet, in spite of an increasing number of studies focusing on this species (e.g., Aymerich and Gosàlbez, 2015;Biffi et al, 2016;Charbonnel et al, 2016;Escoda et al, 2017), the respective influence of prey, competitors and predators on its survival and distribution still remains to be explored.…”
Section: Introductionmentioning
confidence: 99%